Currency options - Coyle, Brian (United Kingdom: Financial World Publishing, 2000)
The book examines the use of derivatives in the foreign exchange markets.
Includes Index
Loans
rua 05/02/15
Keywords: Economics; Foreign exchange market; Money market; Currency options